2016
DOI: 10.1002/polb.24065
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic self‐assembly and gelation in aqueous methylcellulose—theory and modeling

Abstract: Recent experimental studies demonstrated that the aqueous methylcellulose (MC) polymer chains in water can form nanoscale fibrils (diameter $14 nm, persistence length $60 nm), and those fibrils can organize into networks at higher temperatures and/or concentrations, forming the commonly observed gel. Here we propose that the fibrils are onedimensional self-assemblies of stacked, fused polymer rings that are formed at elevated temperatures due to the changing nature of the MC-water hydrogen bonding. This mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 56 publications
(122 reference statements)
4
47
0
Order By: Relevance
“…Interestingly, CD signal was also observed in pure 1.0 wt % MC at 60 °C ( Figure S14 ), possibly related to the existence of ring-like fibrillar structures. 47 49 , 51 , 52 Remarkably, CD signal was detected from MC/CNC gels at as low as 0.5 wt % of CNC in 1.0% MC. Further, the signals of MC/CNC were amplified by increasing CNC weight fractions as well as upon increasing the temperature.…”
Section: Resultsmentioning
confidence: 96%
“…Interestingly, CD signal was also observed in pure 1.0 wt % MC at 60 °C ( Figure S14 ), possibly related to the existence of ring-like fibrillar structures. 47 49 , 51 , 52 Remarkably, CD signal was detected from MC/CNC gels at as low as 0.5 wt % of CNC in 1.0% MC. Further, the signals of MC/CNC were amplified by increasing CNC weight fractions as well as upon increasing the temperature.…”
Section: Resultsmentioning
confidence: 96%
“…For example, it was recently shown that methylcellulose gel contains fibrillar structures with a uniform diameter [ 13 ]. Such structures are likely to be initiated by the collapse of individual methylcellulose chains when the solution temperature increases [ 14 ]. This collapsed state can be qualitatively predicted based on the structural properties of methylcellulose, as explained in a recent simulation study of methylcellulose by Huang et al [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studying the self-assembly of model diblock copolymers having unsubstituted glucose/cellobiose as hydrophilic heads and regioselectively methylated or permethylated glucose units as hydrophobic tails with a total DP of ≤ 28, Nakagawa et al [5] showed the necessity of a sequence of at least 10 permethylated glucosyl units for gelation of methylcellulose to happen. Fibril formation prior to gelation was also observed and further studied using a systematic coarsegrained model [6][7][8][9][10][11][12][13][14]. Taking into account the role of highly methylated glucose units in thermogelation of methylcellulose, Adden et al [15] suggested the cationic ring-opening polymerization of differently substituted cyclodextrins as a potential method for synthesis of glucan ether block copolymers having blocks of permethylated glucose units.…”
Section: Introductionmentioning
confidence: 99%